2019
DOI: 10.1088/1748-9326/ab2dbf
|View full text |Cite
|
Sign up to set email alerts
|

The contrasting effects of farm size on farm incomes and food production

Abstract: Small-scale farming provides both food and livelihoods for the vast majority of the global poor. Thus, increasing and stabilizing farm incomes and food production in developing countries is fundamental to reducing global poverty. Policies for rural development such as improved access to non-agricultural incomes or land titling may benefit farmers, but they may also lead to farm consolidation with unintended consequences for aggregate food supply. Using a large panel dataset of rural households in Uganda, we pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 40 publications
(43 reference statements)
2
23
0
1
Order By: Relevance
“…Additionally, Xaba and Masuku (2013) reported that increasing the size of farms under vegetable production would result in an increase in vegetable profitability by 21.5%; this further confirms the positive influence of farm size on farm income. Similar findings were also reported by Noack and Larsen (2019). However, Das & Ganesh-Kumar (2017) reported a U-shaped association between farm size and farm income, a situation which implies that farm size increases farm income up to a certain level then starts to reduce it.…”
Section: Determinants Of Income From Maize Productionsupporting
confidence: 76%
See 1 more Smart Citation
“…Additionally, Xaba and Masuku (2013) reported that increasing the size of farms under vegetable production would result in an increase in vegetable profitability by 21.5%; this further confirms the positive influence of farm size on farm income. Similar findings were also reported by Noack and Larsen (2019). However, Das & Ganesh-Kumar (2017) reported a U-shaped association between farm size and farm income, a situation which implies that farm size increases farm income up to a certain level then starts to reduce it.…”
Section: Determinants Of Income From Maize Productionsupporting
confidence: 76%
“…When farmers use their input appropriately, they would earn more income from large portions of land due to the benefits that accrue from the economies of scale. A recent study by Noack and Larsen (2019) aimed at determining the effects of farm size on agricultural income in Uganda found out that agricultural income increases with an increase in farm size. Similar findings were also reported by Doti (2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This implies that the landless and those with small land sizes earn less as they have no or little land to farm on, and others have to completely depend on casual labor. These findings are supported by those of [22] who found out that income from agriculture is higher when the size of land is big as compared to when the land size is small. Figure 4 shows the relationship between income bracket and size of land.…”
Section: Sources Of Livelihoodsupporting
confidence: 73%
“…Increased farm size may increase the chances of producing more crops, resulting in increased income and household consumption. According to one study, larger farms increase the variability of local food production, and farmers benefit from having larger farms because they generate more consistent income ( Noack and Larsen, 2019 ). The other socioeconomic variables (HH head literacy and family) did not show a consistent significant influence on HDDS.…”
Section: Discussionmentioning
confidence: 99%